Experimental and Computational Studies on the Reactivity of a Terminal Thorium Imidometallocene towards Organic Azides and Diazoalkanes1. (28th August 2014) - Ren, Wenshan; Zhou, Enwei; Fang, Bo; Hou, Guohua; Zi, Guofu; Fang, De‐Cai; Walter, Marc D.
Abstract The reaction of the base‐free terminal thorium imido complex [η5‐1, 2, 4‐(Me3C)3C5H22ThN(p‐tolyl)] (1) with p‐azidotoluene yielded irreversibly the tetraazametallacyclopentene [η5‐1, 2, 4‐(Me3C)3C5H22ThN(p‐tolyl)NNN(p‐tolyl)] (2), whereas the bridging imido complex [[η5‐1, 2, 4‐(Me3C)3C5H2]Th(N3)22μ‐N(p‐tolyl)2][(n‐C4H9)4N]2 (3) was isolated from the reaction of 1 with [(n‐C4H9)4N]N3. Unexpectedly, upon the treatment of 1 with 9‐diazofluorene, the NN bond was cleaved, an N atom was transferred, and the η2‐diazenido iminato complex [η5‐1, 2, 4‐(Me3C)3C5H22Thη2‐[NN(p‐tolyl)]N(9‐C13H8)] (4) was formed. In contrast, the reaction of 1 with Me3SiCHN2 gave the nitrilimido complex [η5‐1, 2, 4‐(Me3C)3C5H22ThNH(p‐tolyl)N2CSiMe3] (5), which slowly converted into [η5‐1, 2, 4‐(Me3C)3C5H2η5:κ‐N‐1, 2‐(Me3C)2‐4‐CMe2(CH2NNCHSiMe3)C5H2ThNH(p‐tolyl)] (6) by intramolecular CH bond activation. The experimental results are complemented by density functional theory (DFT) studies.